La gestion des espaces ouverts de Lille Métropole - Nicolas Rouget (Projets de Paysage)
As long as they are playing their part in the development of the territory, the farmers of the area of Lille are assigned to share the responsability of the framework of the landsape and environment of their metropolis. The aim of the article is to understand how, and on which conditions, a convergence of interests between farmers and urban planners can be set up. The study, founded on several sets of discussions, brings face to face the agricultural paths and dynamics, together with the distressing route of the development plan of the area of Lille. Thanks to the example of Lille, we can also wonder how efficient the experiments led in the local participation are: a development plan respectful of the landed and agricultural imperatives, together with a diversified agriculture and a partnership based on the contractualisation don’t constitute sufficient conditions to the full achievement of an agriurban project. A participative management of the land involves some continuous efforts of accompaniment and relaunching.